Binding affinity of serum immunoglobulin G to cardiolipin and other phospholipids in patients with systemic lupus erythematosus and syphilis. - Costello, P B (1988)
Qualitative and quantitative assays for human antibodies to cardiolipin and other phospholipids were used in tests for these reactions in sera from patients with systemic lupus erythematosus (SLE) and syphilis. Of 22 SLE serum samples tested by the qualitative assay, 8 showed positive staining to cardiolipin, phosphatidic acid, and/or phosphatidylserine. All 47 syphilitic sera reacted with these three phospholipids. The apparent affinity of anticardiolipin binding was estimated by normalizing absolute binding levels as a function of serum concentration to the maximum percent bound. It was evident that antibody affinity was four- to fivefold lower in the SLE sera than in the syphilitic sera. Twelve serum samples from patients with one or more features of the anti-cardiolipin syndrome demonstrated mean binding values which were not distinguishable from binding in other SLE sera. In sera from patients with active SLE, binding affinity for cardiolipin was somewhat greater than that in samples from patients with inactive disease, but the differences were not statistically significant. The low anticardiolipin binding affinity which was observed in patients with SLE compared with that in patients with syphilis casts doubt on a pathogenic role for these reactions.